A study on India's trade relationship with SAARC countries. (2nd December 2011) - Vadra, Ratna
India occupies 70% of the SAARC region, both geographically and economically, and the remaining six nations of the SAARC borders only with India and not with each other. As the biggest, and the most industrialised trading partner among the SAARC countries, India has to recognise that a special responsibility devolves on her and take a lead in making the Regional Economic Cooperation a reality in South Asia. The present study reveals that there are enormous opportunities for forging closer economic relations among SAARC countries. These opportunities could be fully utilised through the twin processes of trade liberalisation and industrial restructuring which are complementary to each other. The SAARC Preferential Trade Arrangement (SAPTA) is the first step in trade liberalisation. However, the scope of SAPTA has to be sufficiently widened in order to derive substantial benefits from preferential trading agreements. It is suggested that the SAARC countries adopt a combined approach for tariff elimination, tariff reduction and preferential or concessional tariffs. This process will help in moving quickly towards the creation of a Free Trade Area in the SAARC region. This paper studies the India's trade with SAARC countries during the period 1999–2000 to 2009–2010 and examine whether SAPTA is successful in increasing India's intra-regional trade.